N-methylsansalvamide elicits antitumor effects in colon cancer cells in vitro and in vivo by regulating proliferation, apoptosis, and metastatic capacity - Park, Juhee; Moon, Sung-Kwon; Lee, Chan (Frontiers in Pharmacology, 2023)
N-methylsansalvamide (MSSV), a cyclic pentadepsipeptide, was obtained from a strain of Fusarium solani f. radicicola. The current study investigated the anti-colorectal cancer effect of MSSV. MSSV exhibited the inhibition of the proliferation in HCT116 cells via induction of G0/G1 cell cycle arrest by downregulating CDK 2, CDK6, cyclin D, and cyclin E, and upregulating p21WAF1 and p27KIP1. Decreased phosphorylation of AKT was observed in MSSV-treated cells. Moreover, MSSV treatment induced caspase-mediated apoptosis through elevating the level of cleaved caspase 3, cleaved PARP, cleaved caspase 9, and pro-apoptotic Bax. MSSV revealed the declined MMP-9 level mediated by reduction in the binding activity of AP-1, Sp-1, and NF-κB motifs, which led to the migration and invasion of HCT116 cells. In vitro metabolism with rat liver S9 fractions was performed to examine the effect of MSSV metabolites. The metabolic process enhanced the inhibitory effect of MSSV on the HCT116 cell proliferation via decline of cyclin D1 expression and AKT phosphorylation. Finally, oral administration of MSSV inhibited the tumor growth of HCT116 xenograft mice. These results suggest that MSSV is a potential anti-tumor agent in colorectal cancer treatment.